Revealing the hidden gaps: A comprehensive needs analysis for numeracy and financial literacy learning in ratio topics supported by digital and intelligent technologies - Farhan Hamdallah; Pujia Siti Balkist; Djaka Firmansyah Robbiana; Yumi Sarassanti; Novy Anggraini Sudibyo; Krida Singgih Kuncoro (Universitas Sarjanawiyata Tamansiswa, 2025)
Numeracy and financial literacy are widely recognized as essential competencies for students in the twenty-first century, particularly in navigating real-life decision-making contexts. However, empirical evidence consistently indicates that middle school students struggle to apply ratio concepts meaningfully in financial situations. This study aims to conduct an in-depth needs analysis as a foundational step toward the future development of an innovative learning medium that integrates numeracy, financial literacy, digital tools, and intelligent technologies. Using a descriptive qualitative-dominant approach, data were collected through curriculum analysis, classroom observations, teacher interviews, student questionnaires, diagnostic tests, and document analysis. The findings reveal significant gaps between curricular expectations and classroom practices, including the dominance of procedural instruction, limited financial context integration, insufficient use of digital learning tools, and the absence of adaptive or reflective feedback mechanisms. Furthermore, the results indicate that students possess fragmented understanding of ratios and demonstrate low confidence in making financial decisions based on numerical reasoning. These findings highlight the urgent need for a learning medium that supports contextualized reasoning, computational exploration, and reflective guidance. The research contribution of this study lies in providing a rigorous empirical foundation that informs the design requirements of future technology-enhanced learning innovations aimed at strengthening the integration of numeracy and financial literacy in mathematics education.